The Role of Competence, Occupational Safety and Health, Leadership, Work Motivation, Satisfaction and 5R Culture on Performance - Hariyasasti, Yayuk; Purwanto, Agus (AGUSPATI Research Institute, 2025)
In the era of globalization and increasingly tight industrial competition, companies are required not only to achieve production and profit targets, but also to build conducive industrial relations between management and employees. Good industrial relations can create a harmonious, productive, and sustainable work climate. Two important factors that contribute to the creation of healthy industrial relations are employee competence and the implementation of Occupational Safety and Health (K3).Competence has a significant effect on improving employee performance. The implementation of K3 plays an important role in creating a safe work environment and increasing work enthusiasm. The combination of competence and K3 simultaneously improves employee performance and contributes to harmonious industrial relations. Employee competence is an important factor in determining the level of individual performance. Employees who have good knowledge, skills, and work attitudes tend to be able to complete tasks more effectively and efficiently. The implementation of Occupational Safety and Health (K3) has a positive impact on the work environment, creating a sense of security and comfort, and reducing the risk of work accidents. This has a direct impact on increasing employee morale and productivity. Simultaneously, competence and K3 contribute positively to improving employee performance.